Perancangan Sistem Informasi Laporan Pengolahan Data Transaksi Penjualan Dan Persediaan Stok Barang Berbasis Web - Reno Muthmainnah; Firdaus (Universitas Putra Indonesia YPTK Padang, 2022)
The development of information technology in the modern era is currently very rapid and has a significant impact on various aspects of life, including data processing in companies and MSMEs. Data processing that is still carried out traditionally tends to take a long time and has a low level of accuracy and precision. As technology advances, the use of computer-based applications has become a common solution to support data processing and decision-making. The use of computer technology can help improve work efficiency, speed up data processing, and increase the accuracy and precision of the resulting information. OkeStoRen is an MSME engaged in PPOB, selling mobile phone accessories, and various other goods located in Padang City, West Sumatra. In the process of processing transaction data, OkeStoRen still uses traditional methods with paper and pen media, so the recording process is considered ineffective because it requires a long time, has a low level of accuracy, and has a fairly high risk of data loss. Therefore, a computerized data processing system is needed to improve the effectiveness, efficiency, and security of transaction data at OkeStoRen..